Geographic distribution of the hard ticks (Acari: Ixodida: Ixodidae) of the world by countries and territories - Guglielmone, Alberto A.; Nava, Santiago; Robbins, Richard G. (Zootaxa, 2023)
The hard tick family Ixodidae currently comprises 762 species worldwide, but an analysis of the occurrence of these species in the world´s countries, territories, zoogeographic regions (Afrotropical, Australasian, Nearctic, Neotropical, Oriental, Palearctic) and remote islands has not been attempted since 2009. Here, we present and critically discuss distributional data for all currently accepted ixodid species known from 226 countries and territories in six zoogeographic realms. This summary of ixodid tick biogeography should prove to be a valuable reference for biologists interested in ticks as organisms as well as specialists focusing on tick-borne diseases. Data for all species treated here were derived from a literature search that ended on March 31, 2022.